2020
DOI: 10.1038/s41467-020-18041-3
|View full text |Cite
|
Sign up to set email alerts
|

Possible itinerant excitations and quantum spin state transitions in the effective spin-1/2 triangular-lattice antiferromagnet Na2BaCo(PO4)2

Abstract: The most fascinating feature of certain two-dimensional (2D) gapless quantum spin liquid (QSL) is that their spinon excitations behave like the fermionic carriers of a paramagnetic metal. The spinon Fermi surface is then expected to produce a linear increase of the thermal conductivity with temperature that should manifest via a residual value (κ 0 /T) in the zerotemperature limit. However, this linear in T behavior has been reported for very few QSL candidates. Here, we studied the ultralow-temperature therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 75 publications
10
39
1
Order By: Relevance
“…We, therefore, take 10.5 T as the crossover field from the correlated spindisordered state to the spin-polarized state. The magnetization curve further suggests that the saturation field for the B ⊥ b-axis case is around B S = 12.5 T with saturation magnetization M S = 2.01μ B /Co 2+ obtained by subtracting off the Van-Vleck paramagnetic contribution 49 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 85%
“…We, therefore, take 10.5 T as the crossover field from the correlated spindisordered state to the spin-polarized state. The magnetization curve further suggests that the saturation field for the B ⊥ b-axis case is around B S = 12.5 T with saturation magnetization M S = 2.01μ B /Co 2+ obtained by subtracting off the Van-Vleck paramagnetic contribution 49 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 85%
“…Thermal conductivity was measured by using a “one heater, two thermometers” technique in a 3 He/ 4 He dilution refrigerator at 70 mK–1 K, equipped with a 14 T superconducting magnet 72 , 73 . The sample was cut precisely along the crystallographic axes with the longest and the shortest dimensions are along the a - or the c -axis.…”
Section: Methodsmentioning
confidence: 99%
“…The first experimental study reported a sizable antiferromagnetic exchange and no long-range ordering down to 50 mK [27]. Very recently, ultralow-temperature specific heat measurements revealed a magnetic ordering transition at T N = 148 mK [28], i.e.,∼ 20 times smaller than the Weiss temperature θ = −2.5 K obtained from the static magnetic susceptibility χ(T ) [28]. Another interesting observation is the linear dependence of the residual thermal conductivity [28], compatible with the spinon Fermi surface scenario advocated for critical spin liquids.…”
mentioning
confidence: 99%
“…Usually this signifies proximity to a magnetic phase transition where the spin dynamics experiences a critical slowing down [35]. However, such a phase transition in Na 2 BaCo(PO 4 ) 2 takes place at two orders of magnitude lower temperature of T N = 148 mK [28] which evidences an extended lowtemperature regime of the spin-liquid like, slow spin fluctuations in the electron spin system.…”
mentioning
confidence: 99%